2013
DOI: 10.1063/1.4789411
|View full text |Cite
|
Sign up to set email alerts
|

A sequence-dependent rigid-base model of DNA

Abstract: A novel hierarchy of coarse-grain, sequence-dependent, rigid-base models of B-form DNA in solution is introduced. The hierarchy depends on both the assumed range of energetic couplings, and the extent of sequence dependence of the model parameters. A significant feature of the models is that they exhibit the phenomenon of frustration: each base cannot simultaneously minimize the energy of all of its interactions. As a consequence, an arbitrary DNA oligomer has an intrinsic or pre-existing stress, with the leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
133
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(136 citation statements)
references
References 87 publications
2
133
0
Order By: Relevance
“…30 Similarly, the need to describe hybridization rules out those coarse-grained models which are intended just to describe dsDNA and do not dissociate. [31][32][33][34][35][36][37] Therefore, the minimal unit must at most be at the level of a single nucleotide. It is interesting to note that Lankaš et al found that the level of the base also provides a more appropriate level to capture the local dynamics of DNA than that of the base pair.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…30 Similarly, the need to describe hybridization rules out those coarse-grained models which are intended just to describe dsDNA and do not dissociate. [31][32][33][34][35][36][37] Therefore, the minimal unit must at most be at the level of a single nucleotide. It is interesting to note that Lankaš et al found that the level of the base also provides a more appropriate level to capture the local dynamics of DNA than that of the base pair.…”
Section: Introductionmentioning
confidence: 99%
“…The first, which we term the "bottom-up" approach, is to fit the model to results (typically correlation functions) from a finer-grained model, which is usually an empirical all-atom model (e.g. AMBER, CHARMM), [35][36][37]63,64,[67][68][69] although fitting to energies obtained from electronic structure calculations (albeit in the absence of water) 65 has also been performed. The second "topdown" approach is to directly fit the parameters of a physically motivated potential to reproduce measured experimental properties, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The interactions of nucleosomes in these chains mirror the patterns of internucleosomal association captured in mesoscale simulations, and the polymeric behavior reflects these local properties (17). Specifically, the rest states correspond to the mean values of the rigid-body parameters over the set of mesoscale structures, and the range of deformations reflects the covariance of parameters along lines analogous to those used in basepair-level treatments of DNA (6,64).…”
Section: Influence Of Nucleosome Positioning On Higher-order Chromatimentioning
confidence: 99%
“…The elements within the blocks are the elastic moduli governing the fluctuations of parameters for the designated nucleosome pairs. The values are extracted from the covariance of rigid-body parameters along the lines of those used in basepair-level treatments of DNA (6,64). (B) The differences in local nucleosome structure and deformability resurface in snapshots of longer chains captured in nucleosome-level simulations (17), here 300-nucleosome (~50,000 bp) chromatin constructs guided by the rigid-body parameters of oligonucleosomes with (left) 168-bp and (right) 171-bp nucleosome repeating lengths.…”
Section: Future Directions: Bridging the Gap Between Basepair Sequencmentioning
confidence: 99%
See 1 more Smart Citation